2017
DOI: 10.3390/medicines4040070
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Enantiomeric Distribution, and Antifungal Activity of the Oleoresin Essential Oil of Protium amazonicum from Ecuador

Abstract: Background: Protium species (Burseraceae) have been used in the treatment of various diseases and conditions such as ulcers and wounds. Methods: The essential oil from the oleoresin of Protium amazonicum was obtained by hydrodistillation and analyzed by GC-MS, GC-FID, and chiral GC-MS. P. amazonicum oleoresin oil was screened for antifungal activity against Candida albicans, Aspergillus niger, and Cryptococcus neoformans. Results: A total of 54 components representing 99.6% of the composition were identified i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Initially, the programming of the column oven was based on a previous study (Siani et al 2012), in which the authors used a DB-5 column, but poor separation efficiency was found for two of the interesting triterpenes, α-amyrin and lupeol, and several other expected minor peaks. Any pre-treatment to remove monoterpenes and sesquiterpenes was spared since these compounds elute below 200 o C, as also shown by Satyal et al (2017), and so do not interfere with the signals of triterpenes (elution above 290 o C). Thus, GC-FID analyses of PBO in columns with other stationary phases (DB-35, DB-1701, DB-17HT and DB-Innowax) were performed, and typical chromatograms are presented in Figure 1a than the DB-17HT column.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Initially, the programming of the column oven was based on a previous study (Siani et al 2012), in which the authors used a DB-5 column, but poor separation efficiency was found for two of the interesting triterpenes, α-amyrin and lupeol, and several other expected minor peaks. Any pre-treatment to remove monoterpenes and sesquiterpenes was spared since these compounds elute below 200 o C, as also shown by Satyal et al (2017), and so do not interfere with the signals of triterpenes (elution above 290 o C). Thus, GC-FID analyses of PBO in columns with other stationary phases (DB-35, DB-1701, DB-17HT and DB-Innowax) were performed, and typical chromatograms are presented in Figure 1a than the DB-17HT column.…”
Section: Resultsmentioning
confidence: 95%
“…Gas chromatography (GC) with columns using low polarity stationary phases, composed of polydimethylsiloxanes with 1 to 5% phenyl groups, has been usually applied for the chemical analysis of breu. This probably occurs because these columns are efficient in separating the monoterpenes and sesquiterpenes present in the volatile fraction of this oleoresin (Ramos et al 2000;Siani et al 2012;Satyal et al 2017), which has been extensively studied in view of its versatility of applications for the cosmetic industries. Thus, there is a clear tendency to reproduce these analytical conditions in the characterization of the non-volatile fraction of breu, which is rich in triterpenes (Maia et al 2000;Guimarães & Siani 2007;Silva et al 2009;Siani et al 2012;Lima et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The carrier gas was helium with a constant flow rate of 1.8 mL/min. For each essential oil sample, a 3% w / v solution in DCM was prepared, and 0.1 μL was injected using a split ratio of 1:45 [ 24 , 25 , 26 ]. The enantiomer percentages were determined from peak area.…”
Section: Methodsmentioning
confidence: 99%
“…The injector temperature was kept at 260 • C. For each essential oil sample, 1:10 (v/v) solution in dichloromethane (DCM) was prepared and 0.3 µL was injected using a split ratio of 1:30. Identification of the individual components of the essential oils was determined by comparison of the retention indices and comparison of the mass spectral fragmentation patterns (over 80% similarity match) with those found in the MS databases using LabSolutions GCMS solution software version 4.45 (Shimadzu Scientific Instruments, Columbia, MD, USA) [24][25][26]. The relative percentages of the individual components are listed in Table 2.…”
Section: Chemical Composition Analysis By Gas Chromatography/mass Spectrometry (Gc-ms)mentioning
confidence: 99%
See 1 more Smart Citation